Prevalence of Male Sexual Harassment among Female Sports Participants in Greece - Chroni, Στυλιανή; Fasting, Kari (Inquiries in Physical Education and Sport, 2009)
This article presents data from a study that surveyed gender relations in sports. The main objective of the paper is to explore the prevalence of sexual harassment performed by men toward Greek female athletes and exercisers. Three hundred and eight women (Mage = 21.45) who were active in sports either at the international level, the national level, or were exercisers, participated in the study. The results show that overall 71.5% of the participants had experienced some form of sexually harassing behavior from a man. Experiences of sexual harassment performed by men both inside and outside the sport domain were reported. While, variations among athletes’ performance levels and sexual harassment from men outside sport were significant (p<.05) as exercisers reported experiencing significantly more sexual harassment; variations among athletes’ levels and harassment from men inside sport were non-significant. The form of sexual harassment the participants reported experiencing the most was ‘repeated unwanted sexually suggestive glances, comments, jokes, etc’. The findings are discussed in relation to the country’s gender order, gender equality laws as well as the anti-sexual harassment laws inside and outside sport organizations.